Assessment of Heavy Metal Contamination and Sources in Road Dust from the Da Nang's Largest Industrial Zone and Surrounding Areas - Tinh, Nguyen Thi Hong; Ba Quoc, Tran (VNU Journal of Science: Earth and Environmental Sciences; Vol 41 No 2, 2025)
This study assesses the pollution levels and sources of As, Pb, Zn, and Mn in road dust within the most significant industrial zone (IN) in Da Nang and surrounding urban (SU) areas. By collecting and analyzing samples from the IN zone, SU areas, and background (BA) locations, the research revealed that the concentrations of these metals increase from BA areas through SU areas to peak in the IN zone, with the concentration order being As < Pb < Zn < Mn. Spatial distribution analysis of these metals demonstrated significant variations among areas, with the highest concentrations of As observed in the northwest of the IN zone and highest Pb and Zn concentrations in the southeast. Mn exhibited high concentrations within the IN zone and certain hotspots in nearby SU areas. The pollution levels of these metals were calculated using the geoaccumulation index (Igeo), enrichment factor (EF), and pollution load index (PLI). Zn and Pb showed moderate to "solid" pollution levels in the IN zone, whereas Mn and As indicated lower pollution levels. Zn, Pb, and As sources primarily originate from industrial activities such as zinc coating production, thermal insulation products, and cement manufacturing. Mn sources include industrial activities, vehicular emissions, and geological factors. The findings underscore the critical need for enhancing emission controls and efficiently managing waste systems to minimize pollution. This is essential to safeguard community health and maintain a healthy living environment for residents and industries in Da Nang and similar regions globally. Future research directions could focus on longitudinal studies to monitor trends in metal pollution and evaluate the effectiveness of long-term mitigation strategies.